Sport-based corporate social responsibility in European professional football - Männistö, Minna (My University, 2013)
In the past few decades, sport has become a major business with remarkable international reach. As part of the commercial sector of sport, professional sport is said to be intrinsically different from other businesses due to its unique characteristics, such as the peculiar economics and the intense loyalty of fans. Simultaneously with the growing business aspect, sport continues to have great social and cultural impacts on our society. Sport has also become an increasingly popular means of attending social problems due to its alleged suitability for such purposes and its popular appeal. A great number of actors in the professional sport industry have long been involved in socially responsible activities, many of which have been sport-related. While Corporate Social Responsibility (CSR) has been extensively studied in general, its role in the professional sport industry has received less attention in the academic research until recently. It has been argued that due to the unique characteristics of professional sport, CSR should also be studied in this particular context. The objective of this study was to contribute to filling the research gap and increase the understanding of CSR in the context of professional sport by examining sport-related CSR realized by professional football clubs in Europe. The theoretical part of this study leaned on previous literature about using sport as a means of attending social issues and the role of CSR in professional sport industry. The empirical part of the study was carried out through web site analyses and interviews. The clubs to be examined were chosen by using purposive sampling technique and taking into consideration the accessibility and suitability of information the clubs could offer. The method used for analyzing the data was qualitative content analysis. The empirical findings were largely in line with the theoretical framework of the study. The sportrelated CSR of the clubs was concentrated on teaching the participants diverse skills and values, improving their health, encouraging social inclusion, supporting disabled people, and promoting overall participation in sport. The clubs also emphasized the importance of local communities as targets of their CSR. CSR had been an integral part of the clubs’ activities from the beginning, but there were remarkable differences between large and small clubs in terms of structured organization and realization of their CSR. Measuring and evaluation of CSR appeared to be a challenge for most clubs regardless of their size and resources. The motives for the clubs to engage in CSR seemed to be related to the clubs’ values or to their stakeholders’ interests. In general, the clubs’ CSR went beyond what the society is likely to expect from them in legal or ethical sense.